Effect of Firm Growth and Firm Size on Company Value with Earning Per Share As Moderation - Oktaviani, Retno Fuji (EAJ (Economic and Accounting Journal), 2020)
This study aims to analyze the effect of Firm Growth and Firm Size on Firm Value with Earning Per Share as Moderation (Empirical Study Plastics and Packaging Public Companies on the Indonesian Stock Exchange for the Period of 2014 - 2018). The population in this study were 14 companies, then the researchers used purposive sampling technique so that the research sample was obtained as many as 12 companies. The analysis used is multiple linear regression with moderation. The author uses statistical tools, namely SPSS version 24.0 and Microsoft Excel as data tabulation calculations. The results of the study found that firm growth has an negative influence on firm value, firm size has no effect on firm value, while EPS is proven to moderate the effect of firm size and firm growth on firm value.